2019
DOI: 10.3390/ijerph16152686
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome Among Primary Health Care Nursing Professionals: A Cross-Sectional Population-Based Study

Abstract: This research aims at evaluating prevalence and factors associated with metabolic syndrome (MS) in primary health care (PHC) nursing professionals. A multicenter, population-based and cross-sectional study was conducted in a team-tested sample of 1125 PHC nurses in the state of Bahia, Brazil. Sociodemographic, labor, lifestyle and human biology variables were investigated by mean of anamnesis. MS was evaluated according to the criteria of the first Brazilian Guideline for Metabolic Syndrome, which fully adopts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
42
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(52 citation statements)
references
References 43 publications
3
42
0
7
Order By: Relevance
“…The logistic regression models show that age 51-55 increases the chance of MS occurrence 4.051 times in relation to the age of 50 years; age over 55 increases the occurrence 3.279 times. These findings are in line with the study which evaluated prevalence and factors associated with MS in nurses in Brazil [40]. It is similar to other investigations [41,59,60].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The logistic regression models show that age 51-55 increases the chance of MS occurrence 4.051 times in relation to the age of 50 years; age over 55 increases the occurrence 3.279 times. These findings are in line with the study which evaluated prevalence and factors associated with MS in nurses in Brazil [40]. It is similar to other investigations [41,59,60].…”
Section: Discussionsupporting
confidence: 92%
“…In the study of Conceição das Merces et al [ 40 ], 24.4% of examined nurses had MS, but in their study, 52.2% of the population were under 35 years old. The average age in our study was 52.2 years.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…According to previous research conclusions, working character, age, and gender can influence the prevalence of MetS and burnout. 6 , 7 , 8 , 11 According to Schaufeli et al, 23 patients/clients hope to have more concern, care, empathy, and compassion, and the character of job has a continuous and close relationship with patients/clients, the higher the risk of burnout, such as HCWs, police, and teachers. In our results, the working character of the doctor/nurse group echoes the conclusions mentioned in the previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that burnout is positively associated with MetS in nursing staff. 6 , 7 , 8 Moreover, evidence has shown that SCH is associated with burnout and MetS (edges a and b in Figure 1 ). The TSH level is reportedly higher in chronic stress conditions, suggesting that it induces changes in the psycho‐endocrine system.…”
Section: Introductionmentioning
confidence: 95%